2009
DOI: 10.4161/cc.8.14.9026
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition by microRNAs that target the insulin receptor substrate-1

Abstract: We have examined several microRNAs (miRs) indicated by the databases as targeting the signaling pathway of the type-1 insulin-like growth factor receptor (IGF-IR). Most of the miRs tested had multiple targets, as expected, leading to cell death. However, miR145 seemed to affect its tumor suppressor activity largely by downregulating the docking protein of the IGF-IR, the insulin receptor substrate-1 (IRS-1). These results suggest that, despite the many targets provided by the databases, in some cases a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…1 miR-145 inhibits cancer cell growth by targeting the Insulin receptor substrate-1. 41 This miR can downregulate estrogen receptor-α (ER-α) protein expression through direct interaction with two complementary sites within its coding sequence. 42 In the same study it was reported that miR-145 exhibited a pro-apoptotic effect that was Tp53 activation-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…1 miR-145 inhibits cancer cell growth by targeting the Insulin receptor substrate-1. 41 This miR can downregulate estrogen receptor-α (ER-α) protein expression through direct interaction with two complementary sites within its coding sequence. 42 In the same study it was reported that miR-145 exhibited a pro-apoptotic effect that was Tp53 activation-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…ATRA induces down-regulation of IRS-1 (but not IRS-2) in MCF-7 cells and over-expression of IRS-1 causes resistance to ATRA [24]. miR145 down-regulates both the type 1 insulin-like growth factor receptor (IGF-IR) and its docking protein, the insulin receptor substrate-1 (IRS-1), but not the other docking protein, IRS-2, and inhibits growth of human cancer cells [14,15,25]. The differential effect of ATRA on the two IRS proteins suggested a role of miR145 in ATRA action.…”
Section: All-trans Retinoic Acid Increases Mir145 Expressionmentioning
confidence: 99%
“…Previous studies have also identified IGF-I/IRS1 as direct targets of miR-145. 29,30 Importantly, although most of miRNAs have multiple targets, miR-145 seems to affect its tumor suppressor activity predominantly by repressing IRS1, the docking protein of the IGF-IR. 30 Our data have suggested that miR-145 also directly target N-RAS and VEGF-A, further enhancing knowledge about the miR-145-dependent network.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Interestingly, IGF-I/IRS1 was found to be a predominant target of miR-145. 29,30 Therefore, it is reasonable to speculate that miR-145 regulates the downstream genes of IGF-I/IRS1, including N-RAS and VEGF. However, it remains unclear to date whether these two genes are direct targets of miR-145 and whether miR-145 functionally affects angiogenesis.…”
Section: Introductionmentioning
confidence: 99%